Peningkatan Pengetahuan Masyarakat Mengenai Kesehatan Mental di Desa Sejahtera Kecamatan Palolo, Sulawesi Tengah - Kurnia Utami, Indah; Magfirah, Magfirah; Arynesta, Teddy; Songko, Adelia (Jurnal Mandala Pengabdian Masyarakat, 2024)
The Indonesian Health Research and Development Agency revealed that 9.8% of Indonesian population over the age of 15 experience mental emotional disorders. The wider public has the belief that physical health plays a much more important role than mental health for survival. The increase in the percentage of these mental disorders is one result of neglect of mental health. The purpose of this event is to raise public awareness of the importance ofining mental health. The method used is socialization with direct exposure by the publisher using a brochure lefleat which is continued with a discussion and questioning session. The PKM activities are held in the Welfare Village office which is attended by the local community and the village equipment to facilitate the course of activities. As a result of the activity, the community is very enthusiastic and can add knowledge through shared posttest questionnaires. According to the post-test calculations, 87.52% of people are aware of the importance ofining mental health. It can be concluded that this activity is very beneficial to the village community of Sejahtera.